(untitled) (Al-Farooq Journal of Sciences, 2026)
Alkaline water electrolysis is a mature and cost-effective technology for hydrogen production; however, the combined influence of electrolyte concentration, electrolyte type, and electrode material under controlled laboratory conditions requires further systematic evaluation. This study experimentally investigates the coupled effects of electrolyte type (NaOH and KOH), concentration (20–30%), and electrode configuration (stainless steel–stainless steel, nickel–stainless steel, and nickel–nickel) on hydrogen production rate and cell energy efficiency using a laboratory-scale alkaline electrolyzer operated at constant electrical conditions (5 V, 1.5 A). The results demonstrate that increasing alkaline concentration enhances hydrogen production and cell efficiency due to improved ionic conductivity and reduced internal resistance. Stainless steel electrodes exhibited the lowest hydrogen production rate (0.047 mL/s), while pure nickel electrodes achieved the highest rate (0.061 mL/s) and maximum efficiency of 44.17%, confirming the superior catalytic activity of nickel toward the hydrogen evolution reaction. The nickel–stainless steel configuration showed comparable performance (0.060 mL/s; 43.36%), indicating that incorporating nickel active sites significantly improves electrochemical performance while potentially reducing material cost. Comparative analysis between NaOH and KOH revealed similar trends, with both electrolytes converging to nearly identical hydrogen production rates ( 0.0616 mL/s) and efficiencies ( 44.4%) at 30% concentration, suggesting that at sufficiently high concentrations, performance becomes increasingly governed by electrode kinetics rather than electrolyte type. These findings emphasize the critical role of electrode material and electrolyte concentration in optimizing alkaline electrolysis performance and provide practical insights for improving laboratory-scale hydrogen production systems.